Upaya Pemberdayaan Penyandang Difabel melalui Difa Bike - City Tour & Transport di Yogyakarta - Mauriska Ihza Shafira; MC. Candra Rusmala Dibyorini; Nofi Lidia Falaka; Muhammad Taufiq (SOSIO PROGRESIF | Media Pemikiran Studi Pembangunan Sosial, 2022)
People with disabilities are a minority in society whose accessibility to the world of work is still very limited, so many companies refuse people with disabilities when applying for jobs on the grounds that they are unable to work. Thus, there is a need for empowerment efforts for persons with disabilities, given that their space for movement is very limited. From these social problems, it encourages Difa Bike – City Tour & Transport to become a forum for people with disabilities by helping the mobility of people with disabilities so that they can interact and express their aspirations through difabike. This study aims to determine the empowerment efforts for people with disabilities through Difa Bike – City Tour & Transport in Yogyakarta. Data collection techniques used are observation, interviews and documentation. The data analysis technique begins with data collection, data reduction, data triangulation, data presentation and conclusion drawing and verification. The results of this study indicate that the empowerment efforts for people with disabilities through Difa Bike - City Tour & Transport have been carried out well and have been maximized. This can be seen from the real support and appreciation for work motivation for a group of people with disabilities provided by Difa Bike – City Tour & Transport. In addition, the efforts made by Difa Bike – City Tour & Transport have also been able to change people with disabilities from being helpless to being empowered.Keywords : Effort, Empowerment of People with Disabilities, Difa Bike – City Tour & Transport.